O ensino de Física mediado pelas Tecnologias da Informação e Comunicação (TICS): a construção e aplicação de um ambiente hipermidiático para o ensino da natureza da luz - Araújo, Ewerton Souza de (2019)
This work deals with the elaboration and application of a Hypermedia Environment for the Teaching of Optics in High School Physics. Characterized as an Information and Communication Technology (ICT), this environment is organized in a Blog, whose posts bring hypertexts, links, figures, videos and animations related to the study of the nature of light. Among these elements, the animations stand out as the most important, due to their objective of contributing to overcoming the abstraction of the contents. In addition, it is intended to update the Physics Teaching through the active methodologies mediated by the ICTs. For the elaboration of the educational product, the free software Inkscape, Gimp, Synfig Studo, Writer and Blogger were used. The organization of its content, in turn, was based on the Ausubel Significant Learning theory and the Brunner Spiral Curriculum. Its application was through the methodology of the Flipped Classroom, in a class of 2nd year of the Secondary School of the State School Professor José Moacir Teófilo in Arapiraca, AL. The results showed a good acceptance of the product, mainly in relation to the animations, understood as facilitating elements of the understanding of the contents. Despite this, there were requests for improvements, such as inserting audio in the animations and reducing the texts used in the posts. In general, the application research revealed insufficient learning about the content addressed, as a consequence of extrinsic and intrinsic factors to the elaboration of the product.